Calcium chloride connects potato greening and enzymatic browning through salicylic acid - Jingkui Shi; Wenxin Xie; Yanmei Sun; Qingyu Shi; Xin Xing; Qingguo Wang; Qingqing Li (Food Chemistry: Molecular Sciences)
Greening and enzymatic browning are important factors causing post-harvest losses in potatoes. Although they are two different biological processes, there are some common inhibitors between them. Whether there is a correlation between the two has yet to be studies. In this research, we conducted transcriptome analysis of non-greening and greening potatoes, identifying several browning-related genes (polyphenol oxidase genes and peroxidase genes). Compared to non-greening potatoes, greening potatoes exhibited a greater browning degree. And calcium chloride (CaCl2) can inhibit both greening and enzymatic browning. However, the inhibitory effect on potatoes was weakened when treated simultaneously with SA synthesis inhibitor and CaCl2, indicating that CaCl2 can regulate potato greening and browning by affecting internal SA synthesis. Additionally, exogenous SA treatment of potato tubers can also inhibit enzymatic browning. Our study not only demonstrated that CaCl2 and SA can serve as a bridge connecting the potato greening and enzymatic browning, but also provided important references for the development of novel co-inhibitors.